2011
DOI: 10.4103/0019-5154.87161
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of supraglottic larynx with metastasis to all five distal phalanges of left hand

Abstract: Subcutaneous metastasis from carcinoma larynx is a rare presentation and to the phalynx is the rarest. We herein describe a case report of carcinoma supraglottic larynx, which is involving all five distal phalanges of left hand with simultaneous metastases to lung and liver. Acrometastasis is an unusual presentation, which might mimic an infectious or inflammatory pathology. The brief report highlights the importance of clinical awareness of metastatic dissemination to unusual sites in the face of increasing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…We've had 2 cases of laryngeal Squamous Cell Carcinomas (SCC) with subcutaneous metastasis in the neck regions which has been confirmed by tissue biopsy. Laryngeal SCC most commonly metastasizes to lung and liver [6]. Subcutaneous metastasis in this tumor has been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…We've had 2 cases of laryngeal Squamous Cell Carcinomas (SCC) with subcutaneous metastasis in the neck regions which has been confirmed by tissue biopsy. Laryngeal SCC most commonly metastasizes to lung and liver [6]. Subcutaneous metastasis in this tumor has been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…20 They have been reported to occur at different sites all throughout the body such as head, neck, thorax, upper extremities, abdomen, buttock, and lower extremities. [4][5][6][7][8][9][10][11][12]21 (Table 1) elaborates on sites of metastasis, treatments offered and outcomes in patients with skin metastasis in treated cases of SCC larynx. Treatment options such as radiotherapy, chemotherapy, and excision of skin lesions were considered.…”
Section: Discussionmentioning
confidence: 99%
“…3 That too, metastasis to skin in a treated case of SCC of the larynx is extremely rare. [4][5][6][7][8][9][10][11][12] It generally denotes impending distant metastatic spread or locoregional recurrence, and poor prognosis. On review of literature, there were only few reports of cutaneous metastasis in treated SCC of larynx and limited information on potential treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Skin metastasis indicates a poor prognosis. [ 9 ] Berger and Fletcher[ 10 ] in their study reported that length of survival was approximately 3 months after skin metastasis becomes clinically evident in HNSCC. The treatment intent is usually palliative with the available options being surgical excision, chemotherapy, External beam radiotherapy or a combination of these.…”
Section: Discussionmentioning
confidence: 99%